Disease suppression is driven by microbial community properties at fine taxonomic scales - Shan Shan; Isabelle George; Michael D. Millican; Linda L. Kinkel; Richard A. Lankau (Ecosphere)
Abstract The soil microbiome provides essential services in agroecosystems that can increase plant health and productivity, such as disease suppression and growth promotion. A small number of microbial groups have been proposed as main players behind disease suppression, but the complete picture of the underlying mechanisms remains unclear for both functions in many soil systems. Here, we investigated broad and fine‐scale microbial community features for their contributions to disease suppression and growth promotion for potato plants. In a greenhouse study, we grew potato plants in pots sharing a common background soil and inoculated with living soil microbial communities with or without a separate inoculation with Streptomyces scabiei, the causal agent of potato common scab disease. The suppression of common scab and growth promotion abilities of a variety of soil microbial communities were estimated and related to quantitative patterns in microbial community structure. We found that suppression of common scab was mostly driven by fine‐scale microbial community features, especially the diversity within the Actinomycetota phylum. Even though opposing components of microbial community structure might be related to the two functions, disease suppression did not cause a negative trade‐off in growth promotion. This suggests high functional redundancy in growth promotion. It may be possible to improve the multi‐functionality of soil microbial communities by engineering the communities toward optimized disease suppression and growth promotion ability.